GIP Contributions to the Regulation of Centromere at the Interface Between the Nuclear Envelope and the Nucleoplasm - Chabouté, Marie-Edith; Berr, Alexandre (Frontiers in Plant Science, 2016)
Centromeres are known as specific chromatin domains without which eukaryotic cells cannot divide properly during mitosis. Despite the considerable efforts to understand the centromere/kinetochore assembly during mitosis, until recently, comparatively few studies have dealt with the regulation of centromere during interphase. Here, we briefly review and discuss past and recent advances about the architecture of centromeres and their regulation during the cell cycle. Furthermore, we highlight and discuss new findings and hypotheses regarding the specific regulation of centromeres in both plant and animal nuclei, especially with GIP proteins at the interface between the nuclear envelope and the nucleoplasm.